Laporan Kasus: Seorang Anak Laki-Laki 6 Tahun 9 Bulan dengan Appendicitis (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Appendicitis is one of the most common causes of acute abdominal pain in children and is considered a surgical emergency requiring immediate diagnosis and management to prevent serious complications. Diagnosing appendicitis in children is often challenging because the symptoms are non-specific, and the child's ability to articulate complaints is limited. This case report discusses a 6-year-and-9-month-old boy who presented with a chief complaint of lower right abdominal pain accompanied by nausea, vomiting, and fever. Based on the results of the anamnesis, physical examination, and supporting investigations in the form of laboratory tests and abdominal ultrasound (USG), a diagnosis of acute appendicitis was established. The patient then underwent an appendectomy with good recovery and no complications. This case emphasizes the importance of comprehensive clinical evaluation and the use of non-invasive supporting examinations such as ultrasound in establishing the diagnosis of appendicitis in children. It highlights the critical role of timely diagnosis and intervention, which can lead to favorable outcomes and prevent the risk of perforation or other serious complications. Early recognition and appropriate surgical decision-making are key to improving patient prognosis.